Easy Access to Diverse Multiblock Copolymers with On‐Demand Blocks via Thioester‐Relayed In‐Chain Cascade Copolymerization. (2nd March 2023) - Zhang, Ze; Xiong, Yu; Yang, Peng; Li, Yang; Tang, Rui; Nie, Xuan; Chen, Guang; Wang, Long‐Hai; Hong, Chun‐Yan; You, Ye‐Zi
Abstract: Multiblock copolymers are envisioned as promising materials with enhanced properties and functionality compared with their diblock/triblock counterparts. However, the current approaches can construct multiblock copolymers with a limited number of blocks but tedious procedures. Here, we report a thioester‐relayed in‐chain cascade copolymerization strategy for the easy preparation of multiblock copolymers with on‐demand blocks, in which thioester groups with on‐demand numbers are built in the polymer backbone by controlled/living polymerizations. These thioester groups further serve as the in‐chain initiating centers to trigger the acyl group transfer ring‐opening polymerization of episulfides independently and concurrently to extend the polymer backbone into multiblock structures. The compositions, number of blocks, and block degree of polymerization can be easily regulated. This strategy can offer easy access to a library of multiblock copolymers with ≈100 blocks in only 2 to 4 steps. Abstract : A thioester‐relayed in‐chain cascade copolymerization is developed for preparation of diverse multiblock copolymers with on‐demand blocks, in which thioester groups are built in the polymer backbone by controlled/living polymerizations. These thioester groups further serve as the in‐chain initiating centers to trigger the acyl group transfer ring‐opening polymerization of episulfides to extend the polymer backbone into multiblock structures.